Infection with Kaposi's sarcoma-associated herpesvirus (KSHV) and human immunodeficiency virus (HIV) in relation to the risk and clinical presentation of Kaposi's sarcoma in Uganda. - Newton, R; Ziegler, J; Bourboulia, D; Casabonne, D; Beral, V; Mbidde, E; Carpenter, L; Parkin, D; Wabinga, H; Mbulaiteye, S; Jaffe, H; Weiss, R; et al. (2003)
A case-control study from Uganda found that the risk of Kaposi's sarcoma increased with increasing titre of antibodies against Kaposi's sarcoma-associated herpesvirus (KSHV) latent nuclear antigens, independently of HIV infection. Clinically, widespread Kaposi's sarcoma was more frequent among patients with HIV infection than in those without, but was not related to anti-KSHV antibody titres.